Hard Hat Detection Using Deep Learning Techniques - C. Jagadeeswari, Nagamani.G, Sneha.B and Dr. G. NagaSatish (International Journal of Advanced Science and Technology, 2020)
Human works at construction site are hazardous and risky. These jobs include building houses, roads, dams, repair or maintenance of infrastructure. With the increase in this type of work, fatalities also increased. Taking proper measures can help mitigate the number of accidents. A hard hat is one such equipment required for a worker to enter a construction area. A hard hat is personal protective equipment, which looks like helmet to protect the head from injuries. This is predominantly used in workplace environments such as industrial or construction sites      It is necessary to stop a worker who does not wear a hard hat in construction area. It is also vital need for innovating different methods to monitor the safety of the workers at construction sites. This paper aims at developing a system to detect whether workers wear hard hats are not. The input data given to the training set is the image of each worker entering the site. Our system intelligently identifies whether the worker is bears hard hat or not using YOLO algorithm which is much faster algorithm in object identification.